Resketching the Scope and Strength of Nation-State - Nepal, Dilip (Mangal Research Journal, 2020)
The wave of globalization and the impossibility to maintain uniformity within the nation-state, which in itself is characterized by diversities, has reframed the past status of nation-state in the contemporary globe. In this article, the author considers the scopes and strengths of nation-state are diminishing in the contemporary global order, arguing that the pervasive implications of globalization and the emergence of dissident voices within the specific geo-political territories have posed pragmatic problems in the traditional notion and stand strand of nation-state. As globalization has opened newer avenues with wider spaces of opportunities to the people all across the globe, the culture, tradition, religion, language, emotional affinity within the specified communal people, which are considered to be binding aspects of nation-state, don’t sustain the same values as that used to hold in the past. The digital media and communication, advancement of transportation and the flow of knowledge and goods in the postmodern world have been key instruments to the people to transcend national boundary and promote the cross country affinity. Besides, this paper also explores and analyses how an effort to maintain uniformity in structure within particular political geography fails due to its undeniable reality of socio-cultural and economic variations among people within the same territory. If the uniformity and harmony, as assumed, are synonymous to nation-state, why are many countries suffering with civil wars? Hence, this paper attempts to record the practical problems which have created questions on traditionally elated space and scope of nation-state. Moreover, to examine and analyze this situation, the author uses qualitative method.